PERBANDINGAN KEEFEKTIFAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN DISCOVERY LEARNING (DL) DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH - Latifah Hanum; Dhian Arista Istikomah; Padrul Jana (EduMa: Mathematics education learning and teaching, 2019)
This study aims to compare the effectiveness of Problem Based Learning (PBL) and Discovery Learning (DL) learning models concerning of problem-solving abilities of grade students of 4 Pandak Junior High School. This type of research is quasi-experiment with The Nonequivalent Posttest-Only Control Group Design. The population of this research is students grade  state of 4 Pandak Junior High School. The samples for this research are students grade A and students grade B. The instruments of this research are observation, test, and documentation. Then data analysis techniques are a normality test using Kolmogorov Smirnov, homogenity test using Levene’s test, and hypothesis test use T-test with 0,05 as it significantly. The final result of this research are (1) Problem Based Learning (PBL) models in terms of students mathematical problem-solving skills is effective are students grade  of 4 Pandak Junior High School, it analyzed with one sample t-test method and it shown that  ); (2) Discovery Learning (DL) models in terms of students mathematical problem-solving skill is effective are students grade  of 4 Pandak Junior High School, it analyzed with one sample t-test method and it shown that  ; (3) There are differences between Discovery Learning (DL) learning models and Problem Based Learning (PBL) learning models and shown by the Discovery Learning (DL) learning model is more effective than Problem Based Learning (PBL) learning models in terms of problem solving abilities are students grade  of 4 Pandak Junior High School. It is proved with two samples t-test method, and the result is  .